2000
DOI: 10.2166/wst.2000.0620
|View full text |Cite
|
Sign up to set email alerts
|

Separation of oil–water emulsion from car washes

Abstract: The potentials of UF and NF membrane processes have been evaluated for separation of oil water emulsion generated from car washing operations. Using membranes, wastewater can be effectively recycled and fresh water usage could be reduced. The parameters studied were membrane type, emulsifier types, pressure and competing compounds. Both an-ionic and non-ionic emulsifiers were used for the experimental runs. The Ca2+ and Mg2+ were used as the main competitive ions. Results indicate that a polysulfone membrane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Panpanit et al reported that CA UF membranes showed higher permeation flux compared to polysulfone UF membranes in an oil-water emulsion from a carwash [15]. The effect of pure water permeability of the CA membrane on permeation flux in carwash wastewater after flocculation treatment was examined using three kinds of membranes with MWCO of 150,000 Dalton in a laboratory-scale experiment.…”
Section: Effects Of Pure Water Permeability Of a Uf Membrane And Presmentioning
confidence: 99%
“…Panpanit et al reported that CA UF membranes showed higher permeation flux compared to polysulfone UF membranes in an oil-water emulsion from a carwash [15]. The effect of pure water permeability of the CA membrane on permeation flux in carwash wastewater after flocculation treatment was examined using three kinds of membranes with MWCO of 150,000 Dalton in a laboratory-scale experiment.…”
Section: Effects Of Pure Water Permeability Of a Uf Membrane And Presmentioning
confidence: 99%
“…That is why in literature more attention was given to the first problem of membrane fouling, for example Panpanit et al [5] tried to decrease membrane fouling by adding bentonite to the wastewater. An experimental comparison between the performance of different ultrafiltration and nanofiltration membranes also pointed out that applying nanofiltration to recycle the wastewater would result in less fouling in combination with higher retentions [6,7]. However, a systematic study of the feasibility of nanofiltration in the carwash industry is currently missing in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Many particles and chemicals are found in wash water. The concentration and severity of these particulates are usually extrapolated or not considered [1]. Many contaminants of gas-station wastewater have an impact on the environment.…”
Section: Introductionmentioning
confidence: 99%